Optimum process conditions for effective bioconversion of sewage treatment plant sludge by pure bacterial culture - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Khan Chowdhury, Ahmed Jalal (2005)
The treatment of sewage treatment plant (STP) sludge by pure bacterial culture was studied in lab-scale to evaluate the effective and efficient bioconversion through the developed process conditions. A 2-level full factorial (24) design was conducted with the aim of optimization of processes conditions (factors) such as temperature, agitation, pH and inoculum size for the bioconversion of STP sludge through COD removal (response). A second order polynomial model was applied to observe the linear and interaction effects among the factors. Statistical analysis showed that only the pH did not have significant effect on bioconversion. The results with the surface response analysis indicated the optimum values of parameters: temperature, 400C; agitation, 50 rpm; pH, 6; inoculum, 5% (v/v).